IMPLEMENTASI KEPUTUSAN MENTERI PENDAYAGUNAAN APARATUR NEGARA NOMOR 63 TAHUN 2003 TENTANG PEDOMAN UMUM PENYELENGGARAAN PELAYANAN PUBLIK DI PUSKESMAS ARJASA KABUPATEN SITUBONDO - Dini Noor Aini; Jefry Roby Aji Kurboyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Abdurachman Saleh Situbondo, 2019)
The public service sector which is a priority for service improvement and which is always demanded to improve its quality is the health service sector. The health service sector is one of the public services that must be considered quality and improved the quality of service delivery. everyone has the right to live physically and mentally, live, and get a good and healthy environment and the right to obtain health services. After knowing this condition, researchers are interested in conducting research on